Pemberdayaan Ibu Rumah Tangga Melalui Pelatihan Keterampilan Membuat Boneka Dari Kain Perca - Vita Fibriyani; Ratna Zulfarosda; Sulistyawati; Isnawati Lujeng (CV. Multi Kreasi Media, 2023)
This community service activity aims to provide provisions to women, especially housewives, through training in the skills of making patchwork dolls. With these skills, it is hoped that women can be empowered by utilizing their existing potential. This community service was carried out in Kelurahan Sekargadung, Kecamatan Purworejo, Kota Pasuruan. The training participants are housewives who live in Kelurahan Sekargadung. The method of this activity consists of preparation, implementation and evaluation. The results of this training show that: 1) participants have the motivation to take part in the training, this can be seen in the percentage of attendance of 90%. The second benefit of this activity is 2) participants understand that patchwork has a sale value when it is processed and created. This can be seen from the evaluation results regarding the understanding of the manufacturing process, tools and materials for dolls made of patchwork. In addition, 3) participants have the knowledge and skills to make dolls from patchwork and minimize waste from patchwork. Based on this training activity, it can be concluded that making patchwork dolls can be used as one of the activities for empowering women in Kelurahan Sekargadun, Kecamatan Purworejo, Kota Pasuruan.